ENERGY EXPENDITURE KELOMPOK PRE LANSIA DAN LANSIA DI KOTA DAN DESA (Analisis Data Riskesdas 2007) - Rosmalina, Yuniar; Permaesih, Dewi (GIZI INDONESIA, 2010)
The objective of the study was to determine physical activity level and factors related to physical activities obf Pre Elderly and Elderly people. Methods: The Riskesdas 2007 data was analyzed to fulfill the objective of the study. The sample were household who has aged 45 – 60 years old, no indication of infectious diseases and can independently perform their mobility. The sample was 200.703 Pre Elderly and elderly included in this study. The variable analysis were characteristic of respondent, physical activity level, body weight, height and body mass index , sex, education level. Results: The physical activities of 72,9 percent male Pre-Elderly in Rural was classified as heavy compared to elderly male in Urban (41,4 %). The same pattern of physical activities were indicated in Elderly 50,3 % in rural were considered as heavy level compared to elderly in Urban (25,5%). The pre-elderly women who had physical activities heavy level was higher in Rural (38,9 %) compared to pre-elderly in urban (13,4%). While in elderly women also shown the same pattern 20,5 % in Rural and 7,3% in Urban. The average energy expenditure of pre-elderly male in urban was 2192 ± 132 Kcal and 2192 ±135 Kcal in Rural, while the energy expenditure of male elderly in urban was 1731 ± 120 and 1731 ± 120 Kcal in Rural. The average energy expenditure of pre-elderly women was 1753 ± 69 Kcal in urban and 1744 ±7 2 Kcal in rural, while the energy expenditure of elderly women in urban was 1518 ± 79 and 1503 ± 79 Kcal in rural. Conclusion: There was no differences between theaverage energy expenditure of pre-elderly in urban and rural, while in elderly male was higher in urban compared to rural. The average energy expenditure of pre-elderly and elderly women was higher in urban compared to rural.Keywords: energy expenditure, pre-elderly an d elderly, physical activities